TranspoInfo- A Real-Time Web Application (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We all Familiar with that, In India approx 75% of Public uses Public Transportation Service in their daily life, and majority of public in cities (Delhi, Mumbai) Prefer Buses and Metro-Trains to reach their offices at time. Through this paper we have solved the major problem which the public faces Every day in Delhi, by finding bus stops, perfect location and bus timings. In this paper we have implemented a web application which is a user interface application and can easily work in mobiles and desktops. In our paper we have approached two methods: [1.] Primary Research:- We have Performed a survey in which we did a questionnaire from 15 Delhi residents about what problems they face in the transportation system . [2.] Secondary Research:- Under this research we have gone through many famous web services and app services which are being provided in Delhi, In this case study we solved the major daily life issue which public faces of Delhi in the Transportation System.